Timing of lymphocyte activation in neonates infected with human immunodeficiency virus. - Gallagher, K (1997)
Human immunodeficiency virus (HIV) infection in children is associated with qualitative and quantitative changes in the peripheral lymphocyte surface phenotype beyond the normal maturational changes. Neonates, however, have been reported to have a delayed immune response to HIV compared to HIV-infected adults. We prospectively performed immunophenotyping of T lymphocytes by three-color immunofluorescent labeling and laser flow cytometry to determine the timing of phenotypic alterations in 112 neonates born to HIV-infected mothers. Serial testing was performed at birth (cord blood) and at 2, 6, and 12 weeks of age. Data were divided retrospectively for analysis into those for HIV-infected (n = 14) infants and those for exposed, uninfected infants. Our results show that both infected and uninfected infants had a decline in the percentages and numbers of CD4 cells beginning at 2 weeks of age but that the decline was greater in the HIV-infected group. The activation and differentiation of CD8 T cells in HIV+ infants were shown by a significant increase in CD45RA- CD45RO+ CD8+ cells by 6 weeks of age and by increases in CD8+ S6F1+ CD3+ cells and HLA-DR+ CD38+ CD8+ cells by 2 weeks of age. These results indicate that HIV-infected neonates show alterations in T-cell phenotype reflecting those reported for older HIV-infected children. Most importantly, neonatal T cells are able to respond to HIV within the first weeks of life.